On The Sustainability of External Debt: Is Debt Relief Enough? - Annalisa Prizzon; Gianni Vaggi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2009)
Elaborating on PAsinetti (1998), the 'Geometry of Debt Sustainability' - GDS - represents a simple analytical tool for the analysis of the long run sustainability of foreign debt. GDS provides a simple analysis of three aspects of debt sustainability. It points up how the 'structural' aspect - NICA, the non-interest current account - is closely interlinked with the purely 'financial' aspect. The paper focuses on low income countries, LICs, which face several daunting tasks at once: economic growth, human development and regular debt service. Therefore GDS is also used to analyse the 'human development' aspect of debt sustainability. By considering the three aspects together it emerges that there might be a very stringent trade-off between regular debt service and human development expenditures. All the more so because mosto LICs suffer from structural NICA deficits and GDS highlights the fact its improvement is a anecessary condition to achieve long-run debt sustainability. However, export diversification and the building of stronger trading capacities take time. GDS shows why both debt cancellation and additional aid are necessary to give indebted low income economies a chance to improve both human development and long-run economic viability.
Keywords: E60; H60; O11; 330; debt relief; external debt sustainability; development finance; Internationale Staatsschulden; Schuldenmanagement; Nachhaltigkeit; Entwicklungsländer; Entwicklungsländer